1989
DOI: 10.1144/jm.8.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the Foraminiferal Genera <i>Laterostomella</i> De Klasz and Rérat and <i>Streptochilus</i> Brönnimann and Resig

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Planktic species most tolerant of hyposaline conditions (salinities range of 30.5‰-31‰) are Globigerina bulloides, G. quinqueloba, Globigerinita uvula, Globigerinoides ruber, Neogloboquadrina pachyderma (f. superfi ciaria), and Orbulina universa (Be and Tolderlund, 1971). These hyposaline tolerant species are absent in the Bouse Formation in the Blythe basin, whereas species common in normal marine salinities like Streptochilus are present (Darling et al, 2009;De Klasz et al, 1989). Living Streptochilus are present principally in surface marine waters (Darling et al, 2009;De Klasz et al, 1989;Smart and Thomas, 2006), although oxygen isotope values suggest that Streptochilus can live deeper in the upper water column in temperate to tropical, highly productive waters or in shallow surface waters close to upwelling zones in coastal regions (Resig and Kroopnick, 1983;Hemleben et al, 1989;Smart and Thomas, 2006).…”
Section: Paleontologymentioning
confidence: 99%
“…Planktic species most tolerant of hyposaline conditions (salinities range of 30.5‰-31‰) are Globigerina bulloides, G. quinqueloba, Globigerinita uvula, Globigerinoides ruber, Neogloboquadrina pachyderma (f. superfi ciaria), and Orbulina universa (Be and Tolderlund, 1971). These hyposaline tolerant species are absent in the Bouse Formation in the Blythe basin, whereas species common in normal marine salinities like Streptochilus are present (Darling et al, 2009;De Klasz et al, 1989). Living Streptochilus are present principally in surface marine waters (Darling et al, 2009;De Klasz et al, 1989;Smart and Thomas, 2006), although oxygen isotope values suggest that Streptochilus can live deeper in the upper water column in temperate to tropical, highly productive waters or in shallow surface waters close to upwelling zones in coastal regions (Resig and Kroopnick, 1983;Hemleben et al, 1989;Smart and Thomas, 2006).…”
Section: Paleontologymentioning
confidence: 99%
“…(2006) suggested that Streptochilus martini evolved in the middle Eocene from Chiloguembelina ototara. There is a stratigraphic gap in the upper Oligocene from which no biserial planktics have been described (Kennett and Srinivasan 1983;De Klasz et al 1989). …”
Section: Biserial Planktic Foraminiferamentioning
confidence: 99%
“…south of India, but they were not named, not described at the species level, and not figured. De Klasz et al (1989) named that species S. globulosus, a smooth-walled species, which had been thought to have a Plio-Pleistocene range (Kennett and Srinivasan 1983;Resig 1989). In contrast, Hemleben et al (1989) and Schmuker and Schiebel (2002) state that there is only one living species, which (Kennett and Srinivasan 1983;Resig 1989).…”
Section: Text-figurementioning
confidence: 99%
See 1 more Smart Citation
“…The youngest species, S. globulosum, occurs in the surface sediments of the Ontong Java Plateau and has been found in plankton samples from the Indian Ocean (D. Kroon in De Klasz et al, 1988), establishing it as an extant species. It has a continuous range and is the only biserial species present from just before the first left-to-right coiling change of Pulleniatina in Zone N19/N20 to the present.…”
Section: Species Rangesmentioning
confidence: 99%